Assessment of the potential of native yeast isolated from industrial residual waters in the removal of azoic dyes - Manuela Bolivar-Correa; Ana Maria Gaviria-Villa; Lina Maria Lopez-de Avila (Actualidades Biológicas, 2022)
Azo dyes, widely used in the textile industry, release contaminating effluents that affect different organisms due to their toxicity and recalcitrant nature. Recognizing the role of yeasts in the bioremediation of different contaminated environments, the objective of this study was to evaluate the potential of native yeasts isolated from contaminated water sources in the removal of the azo dye Novasyn blue light BLR. We isolated 15 yeast colonies able to grow in the presence of Novasyn blue light BLR dye and determined their ability to remove the dye in a synthetic medium, obtaining colonies with removal percentages greater than 60%. We selected one colony, MA011, identified as Hanseniaspora opuntinae, to evaluate the effect of the culture media composition, pH, and dye concentration on the removal capacity of the yeast. The results showed that dye concentration and pH have a significant effect on the removal percentage. In addition, differing dye concentrations on the growth and removal capacity of H. opuntinae were evaluated, with a toxic effect of the dye not observed up to 2000 ppm. However, we found that high dye concentrations decreased the removal capacity of the yeast. Finally, we evaluated the removal capacity of H. opuntinae in wastewater, observing no changes in the spectrophotometric profile of the dye before and after the interaction with the yeast, suggesting that dye removal by H. opuntinae occurs by biosorption.